P097 Intracellular interleukin-1 receptor antagonist released upon cell death acts as an alarmin inhibitor in aldara cream-induced psoriasis-like skin inflammation. (March 2019) - Martin, P; Palmer, G; Rodriguez, E; Palomo, J; Gabay, C
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: The inflammatory effects of interleukin (IL)-1 are tightly controlled by IL-1 receptor antagonist (IL-1Ra), which blocks the binding of both IL-1α and IL-1β to IL-1R1. Four IL-1Ra isoforms are produced from the same gene by the use of different first exons, alternative mRNA splicing and translation initiation sites. One IL-1Ra isoform is secreted (sIL-1Ra), whereas the three others are intracellular (icIL-1Ra1, 2, 3) due to the absence of a signal peptide. In contrast to the well-characterized function of the secreted isoform, the biological role of the intracellular isoforms remains largely unclear. The icIL-1Ra1 isoform is constitutively expressed and represents the major isoform in keratinocytes. Objectives: To investigate the role of icIL-1Ra1 in a mouse model of psoriasis-like skin inflammation induced by Aldara cream, an FDA-approved drug with the active ingredient imiquimod, a toll-like receptor 7 agonist. Methods: We generated a mouse line specifically lacking icIL-1Ra1, in which expression of the other three IL-1Ra isoforms was not affected. Psoriasis-like skin inflammation was induced on mouse ears by the topical application of Aldara cream. Skin inflammation was assessed using a caliper to measure ear thickness. Ear mRNA levels of cytokines were measured by real-time PCR. An intracellular or extracellular role of icIL-1Ra1 was investigated ex vivo on ear biopsies and in vitro in primary keratinocytes by real-time PCR or ELISA. Results: Naïve icIL-1Ra1 deficient mice exhibited a normal phenotype. However icIL-1Ra1 deficiency resulted in an enhanced severity of Aldara cream-induced skin inflammation as demonstrated by increased ear thickness. In addition, mRNA levels of several pro-inflammatory cytokines were significantly increased in icIL-1Ra1 deficient mice as compared to wild-type (WT) littermates. By immunofluorescence IL-1Ra was detected only in keratinocytes of naïve and Aldara-treated WT mice, but totally absent in icIL-1Ra1 deficient mice. Using ear biopsies and keratinocytes from WT mice, we observed that Aldara cream led to the release of both icIL-1Ra1 and the alarmin IL-1α, accompanied by caspase 1/11-independent cell lysis. Injection of neutralizing anti-IL-1α antibodies into Aldara-treated icIL-1Ra1 deficient mice significantly reduced the severity of skin inflammation. Conclusions: These data suggest that icIL-1Ra1 is stocked in keratinocytes in order to immediately counteract the inflammatory effects of IL-1α that is released upon cell lysis, thus acting as an intrinsic alarmin inhibitor. Disclosure of Interest: None declared.